A new species of the genus Diaphanes Motschulsky (Coleoptera: Lampyridae) from Gaoligong Mountains of Yunnan, Southwest China - Li, Xueyan; Liang, Xingcai (Zootaxa, 2007)
A new species, Diaphanes pectinealis Li & Liang, from Gaoligong Mountains of Yunnan, Southwest China, is described. Individuals of this species are characterized mainly by the long and strongly pectinate antennae in males and the greatly developed and sclerotized incurved lobe along the dorsal inner margin of male parameres. The characters of the new species challenge the traditional generic diagnoses of Diaphanes and the limits between Diaphanes and its similar genus Pyrocoelia, and reinforce the necessity of a taxonomic revision on these two genera. The types are deposited in Kunming Institute of Zoology, Kunming, and Institute of Zoology, Beijing, the Chinese Academy of Sciences. A checklist of known Chinese Diaphanes species is provided.